If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7y + -10 = 5y + -2 Reorder the terms: -10 + 7y = 5y + -2 Reorder the terms: -10 + 7y = -2 + 5y Solving -10 + 7y = -2 + 5y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-5y' to each side of the equation. -10 + 7y + -5y = -2 + 5y + -5y Combine like terms: 7y + -5y = 2y -10 + 2y = -2 + 5y + -5y Combine like terms: 5y + -5y = 0 -10 + 2y = -2 + 0 -10 + 2y = -2 Add '10' to each side of the equation. -10 + 10 + 2y = -2 + 10 Combine like terms: -10 + 10 = 0 0 + 2y = -2 + 10 2y = -2 + 10 Combine like terms: -2 + 10 = 8 2y = 8 Divide each side by '2'. y = 4 Simplifying y = 4
| -6x-9y=54 | | (9m^3+4n)+7m^3= | | 21-11=5(x-1) | | 8-9x=104-37x | | 6x-2=x-0 | | 6f-14+26-3f-15f= | | -6x+2=1 | | -121-8x=8x+23 | | y^2+3y-16=y-1 | | 3(y-2)=12 | | X^2+19x+K= | | -x=3+2x+16 | | 68=-4(5x+3) | | -10x-106=29-5x | | -21(3t)= | | 28m^2+28m-56=0 | | a+1.6b=8 | | 1.6x-1.2+2.29x=0.28 | | a^2-15a+54=0 | | -102-4x=2x+30 | | -8-3x=8-7x | | 4x+2=7x-12 | | 2.75-0.5t=5-2t | | 8x+5-x=12 | | -2y+3-10=4(2+y)-y | | 2a(a+3)+3a(a+3)= | | [b^3(9-5.9)]= | | 2x(4+x)=8 | | 3-2y+8=4y+6 | | 3(x-1)=5x-10 | | x-40=2x+6 | | 7x-5=2x+4 |